PENGARUH PELATIHAN DAN KOMPENSASI TERHADAP PRESTASI PENGEMBANGAN PROFESI PAMONG BELAJAR SKB SE-JAWA TENGAH DENGAN KOMITMEN ORGANISASIONAL SEBAGAI MEDIASI (Students' Journal of Accounting and Banking, 2013)
The study will take the research object SKB officials learned of Central Java which have professional development training officials learned in 2011 and 2012. Professional development is an essential task of supporting officials learned in implementing the teaching and learning activities, assessment of program and development of a model. Employees’ achievement is affected by the achievement of organizational commitment. Good achievement is also supported by the development of employees through training and giving compensation. This research aimed to analyze the effect of training on organizational commitment, analyzing the influence of compensation on organizational commitment, analyzing the effect of professional development training, analyzing the effect of compensation to the achievement of professional development, analyze the influence of organizational commitment to the achievement of professional development officials learned. The research conducted is an explanatory survey research. The research takes sample of 100 respondents using techniques census officials learned that all professional development trainee in 2011 and 2012. Data analysis technique used is descriptive analysis, analysis instrument (validity and reliability), testing the model (regression, F-test, coefficient test determination), hypothesis testing (t test) and testing mediation effects. Partial test results are positive and significant effect of training on organizational commitment, there is a partial negative effects and no significant compensation to organizational commitment, there is a partial negative effects and no significant compensation to organizational commitment, there is a partial positive and significant impact professional development training to achievement, there is a partial positive and significant effect of compensation to achievement of professional development, there is a partial but significant positive effect of organizational commitment to the achievement of professional development officials learned. Test results are not organizational commitment mediates mediation training and compensation to the achievement of professional development.   Keywords: training, compensation, organizational commitment and achievement